(untitled) (International relations and international law Journal, 2018)
The article is devoted to the critical analysis of Art. 1085 of the Civil Code of the Republic of Kazakhstan – «Qualification of legal concepts (legal qualification)», providing reglamentation of one of most complicated mechanisms of application of choice-of-law rules. Having analyzed the Article`s formulation in context of doctrine, judicial practice, and foreign legislation, the author makes 6 remarks on the Code`s rules and drafts own proposals on their improvement. The authors claims for refusal of wording «Qualification of legal notions», defining it as the most defective elements of the rule reasoning misunderstanding and contradictions in its interpretation. Instead of ephemeral uniform rule the author offers to draft the separate clear criteria of qualification respectively to the subjects: legal relationship or its elements, connection factor, a foreign substantive law rule, and also qualification in renvoi. Key words: qualification (characterization, classification in private international law), qualification lege fori, qualification lege causae.